1991
DOI: 10.1002/cne.903070210
|View full text |Cite
|
Sign up to set email alerts
|

An electron microscopic, immunogold analysis of glutamate and glutamine in terminals of rat spinocerebellar fibers

Abstract: A semiquantitative, electron microscopic immunocytochemical procedure based on the use of colloidal gold particles as markers was employed to analyze the subcellular distribution of glutamate and glutamine, a major glutamate precursor, in a subpopulation of spinocerebellar mossy fiber terminals. These terminals were identified by anterograde transport of a horseradish peroxidase-wheat germ agglutinin conjugate, injected in the thoracic spinal cord. Gold particles signalling glutamate-like immunoreactivity were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
41
1

Year Published

1992
1992
1998
1998

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 46 publications
9
41
1
Order By: Relevance
“…In this study, the presence of peroxidase reaction product in GAD 67 -labeled nerve terminals did not appear to cause any significant quenching of immunogold labeling for GABA, as has been reported in other studies (e.g., Ji et al 1991) because there was statistically higher GABA immunogold labeling over peroxidase-containing (i.e., GAD 67 -positive) nerve terminals. Moreover, our quantitative results support the general observation of Maxwell et al (1989) that GAD-positive nerve terminals were more heavily labeled for GABA than GAD-negative terminals.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, the presence of peroxidase reaction product in GAD 67 -labeled nerve terminals did not appear to cause any significant quenching of immunogold labeling for GABA, as has been reported in other studies (e.g., Ji et al 1991) because there was statistically higher GABA immunogold labeling over peroxidase-containing (i.e., GAD 67 -positive) nerve terminals. Moreover, our quantitative results support the general observation of Maxwell et al (1989) that GAD-positive nerve terminals were more heavily labeled for GABA than GAD-negative terminals.…”
Section: Discussionsupporting
confidence: 86%
“…One of the routes through which transmitter Glu may be formed is through deamidation of Gln (Fonnum, 1984;McGeer and McGeer, 1989), and it appears reasonable that high Glu:Gln ratios should be present in terminals that release and have a high turnover rate of Glu. Indeed, in recent studies on the cerebellar cortex (Ottersen et al, 1991;Zhang et al, 199 l), high Glu:Gln ratios were found in parallel and mossy fiber terminals whereas in comparison to these terminals the ratios in other tissue compartments were low or moderate. Concerning Gln-LI in the VPL, it would be helpful to have more complete immunogold data on types of structures other than those given in the present report before further conclusions are made.…”
Section: General Comments On Glutamate Immunohistochemistrymentioning
confidence: 95%
“…The explanation for different concentrations of Glu in glutamatergic terminals is not clear. In Glu immunogold-labeled preparations, a relationship between the density of gold particles and the packing density of synaptic vesicles has been observed in individual terminals or among terminals of the same type (Montero and Wenthold, 1989;Ottersen et al, 1990b;Ji et al, 1991). The higher packing density of vesicles in RS terminals as compared to CTT and RL terminals (Blomqvist et al, 1985b) could thus explain the higher content of Glu-LI in RS terminals.…”
Section: General Comments On Glutamate Immunohistochemistrymentioning
confidence: 97%
See 1 more Smart Citation
“…When the rats went into a coma, they were given an injection of pentobarbital (100 mg / kg, i.p.) and fixed by perf usion through the heart with glutaraldehyde and formaldehyde (see above) (Ji et al, 1991). Blood samples for glucose analysis were taken immediately before the fixation.…”
Section: Methodsmentioning
confidence: 99%